Tradisi Animisme dan Dinamisme dalam Masyarakat Tigo Luhah Tanah Sekudung - Faras Puji Azizah (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2023)
This paper examines the traditions of animism and dynamism in the Tigo Luhah Tanah Sekudung community. As it is known that this society is known as a religious society, the teachings of Islam play an important role in directing the behaviour of people's daily lives. Nevertheless, in reality, some pre-Islamic elements still develop in society. This research explores elements of animism and dynamism traditions in the Tigo Luhah Tanah Sekudung community. The method used in this study is qualitative, with data collection carried out in several stages, namely by observation, interviews, literature review and documentation. Based on the research conducted, the researchers found that the people of Tigo Luhah Tanah Sekudung still believe in and practice the teachings of their religion and traditions of animism and dynamism. The researchers found animism, including Asyeik, Pelaho Ngambik Aman, Pelaho Ngayun Luci, Pelaho Connect Surat, Pelaho Janem, Mutik Smen, Nahan Ayi Ujan. At the same time, the dynamism is Tangkan and t'place ninek. Some people believe and assume that a certain object has magical powers and can provide help. This belief smells of superstition and heresy that have melted into a form of public belief that is difficult to eliminate in everyday people's lives. Even so, some of the Tigo Luhah Tanah Sekudung Community have started to abandon things that smell animism and dynamism because this is strictly prohibited in Islam.